Developing RADEC Learning Model to Strengthen Religious Character and Critical Thinking in Elementary Schools - Nana Suryana; Wahyu Sopandi; Yadi Ruyadi (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
This research aims to develop a valid RADEC-based learning model for strengthening religious character values and improving critical thinking skills of elementary school students. The study employed a Research and Development (R&D) approach, limited to the stages of preliminary study, model design, expert validation, and revision. The RADEC learning model was developed by reconstructing its syntax Read, Answer, Discuss, Explain, and Create—through the explicit integration of religious character values and critical thinking indicators at each stage of the learning process. Data were collected using expert validation sheets completed by learning model experts and subject matter experts. The validation aspects included the suitability of learning objectives, clarity of RADEC syntax, integration of religious character values, integration of critical thinking skills, and overall feasibility of the model. Data were analyzed using descriptive quantitative techniques based on average scores. The results of expert validation showed average scores ranging from 4.4 to 4.6, which fall into the very valid category for all assessed aspects. These findings indicate that the developed RADEC-based learning model meets validity criteria and is conceptually feasible for use in elementary education. Therefore, the model can be used as a validated learning model prototype that may be further tested for practicality and effectiveness in future research to support character education and critical thinking development in line with the Pancasila Student Profile